Aetanthus confusus, a new species of Loranthaceae (Santalales) from the Colombian Andes - Arango-Carvajal, Susana M.; Caro-Ayala, Heidy; Suescún, Diego; Murillo-Serna, Jhon S. (Phytotaxa, 2026)
Aetanthus confusus, a new species of hemiparasite from the northern part of the Eastern Cordillera of Colombia, is described and illustrated. This species can be recognized by the combination of percurrent branches, stems trigonous, becoming pseudo-quadrangular at maturity, oblanceolate to lanceolate leaf blades with an obtuse or acute apex, and inflorescences composed of triple dyads. The most similar species is A. colombianus, which differs by having stems always trigonous, widely elliptic leaf blades with a rounded apex, and inflorescences composed of double dyads. The new taxon is restricted to the Eastern Cordillera of the Colombian Andes and is considered endangered due to habitat loss. The morphological affinities of Aetanthus confusus with the remaining Aetanthus species are discussed.